Proceedings of the 1st International Conference on Life, Innovation, Change and Knowledge (ICLICK 2018) 2019
DOI: 10.2991/iclick-18.2019.48
|View full text |Cite
|
Sign up to set email alerts
|

The Synergy Of Penta-Helix Stakeholders In The Development Of Smart Destination In Dieng Tourism Area, Central Java - Indonesia

Abstract: This research intends to obtain information about comprehensive picture about penta-helix synergy in realizing the concept of smart tourism in Dieng Central Java. This research uses a qualitative research design with phenomenographic approach that seeks to understand the perspective [1], thought, and experience of stakeholders regarding the synergy among stakeholders (penta-helix) in realizing smart tourism in Dieng Central Java. The results show that there are a number of problems related to the synergicity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
1
3
0
2
Order By: Relevance
“…One of the important outcomes of the workshops was the understanding that solutions to the problems should be realized by inter-agency coordination. This result is consistent with previous studies (Adu-Ampong, 2017;Akça, 2006;Bello et al, 2016;Durgun, 2007;Erfani & Roe, 2020;Eyassu et al, 2019;Hatipoglu et al, 2016;Kantawateera et al, 2013;Ladkin & Bertramini, 2020;Suherlan et al, 2018;Wan & Pinheiro, 2014;Yuksel et al, 1999;Zengingönül et al, 2012) which emphasize the lack of coordination and cooperation as among the important obstacles in sustainable tourism development and planning. For coordination issues, although a consensus was reached on the establishment of a platform in the workshops, the follow up session revealed that no action had been taken.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…One of the important outcomes of the workshops was the understanding that solutions to the problems should be realized by inter-agency coordination. This result is consistent with previous studies (Adu-Ampong, 2017;Akça, 2006;Bello et al, 2016;Durgun, 2007;Erfani & Roe, 2020;Eyassu et al, 2019;Hatipoglu et al, 2016;Kantawateera et al, 2013;Ladkin & Bertramini, 2020;Suherlan et al, 2018;Wan & Pinheiro, 2014;Yuksel et al, 1999;Zengingönül et al, 2012) which emphasize the lack of coordination and cooperation as among the important obstacles in sustainable tourism development and planning. For coordination issues, although a consensus was reached on the establishment of a platform in the workshops, the follow up session revealed that no action had been taken.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, this participation does not necessarily result in full collaboration (Adu-Ampong, 2017). As for a study conducted in Central Java, Indonesia, no common vision of the stakeholders and a lack of cooperation and coordination among tourism actors, government, and other stakeholders were shown as the problems associated with synergy in the application of smart tourism (Suherlan et al, 2018).…”
Section: Lack Of Coordination and Cooperationmentioning
confidence: 97%
“…Penelitian dari Lagarense et al (2018) mengenai pemanfaatan teknologi dan inovasi digital pada pengembangan sport tourism dengan pendekatan Penta Helix di Bali dengan hasil bahwa, pemanfaatan teknologi telah digunakan dengan optimal. Terdapat penelitian dari Suherlan et al (2019) mengenai sinergi Penta Helix dalam mewujudkan konsep smart tourism di Dieng Jawa Tengah. Hasil penelitian terdapat permasalahan sinergisitas Penta Helix dalam penerapan smart tourism.…”
Section: Pendahuluanunclassified
“…Research of the penta helix strategy in developing tourism villages has also been discussed by Suherlan et al [13] entitled "The Synergy of Penta-Helix Stakeholders in the Development of Smart Destination in Dieng Tourism Area, Central Java -Indonesia". The researchers discovered certain issues with synergy in the implementation of smart tourism in the Dieng Tourism Area, due to the lack of a shared vision among stakeholders and the absence of established collaboration and coordination between tourism industry, governmental, and associated parties.…”
Section: Introductionmentioning
confidence: 99%